A religião civil na filosofia política de Rousseau - Zimmermann Júnior, Giovani Luiz (2017)
Rousseau in his book The Social Contract idealizes political principles that guarantee individuals a state where people are free to live without dependence or tyranny on the part of others. Religion has an important role to play in this ideal because it produces "feelings of sociability," as well as helpi77ng to make people aware of the law. For a long time religion exercised influence and power in the politics of nations, it became fundamental to societies that possessed a species of "public spirit," which would facilitate social bonding. It aims at overcoming the constant clash between the powers: secular and religious, he reflected and instituted something "essential" that improves human relations, that maintains peace among citizens. Jean-Jacques does not aim at renouncing the principle of the secular state and freedom of conscience, but he has not yet freed himself from the idea usual in his day, there can only be morality among citizens with the indispensable existence of religion. Civil religion is not like the others of its time, because it has no temples, nor structure of power, it is "purely civil." They are simple, objective dogmas, which aim to foster the virtues of good citizenship, the realization of freedom and equality, based on the general will, as well as total dedication to the country, already consolidated through the social pact.